Overexpression of BAX INHIBITOR-1 Links Plasma Membrane Microdomain Proteins to Stress. Issue 2 (21st August 2015) - Ishikawa, Toshiki; Aki, Toshihiko; Yanagisawa, Shuichi; Uchimiya, Hirofumi; Kawai-Yamada, Maki
Abstract : Overexpression of a cell death suppressor modulates sphingolipid and protein composition of plasma membrane microdomains, leading to enhanced tolerance to stress. Abstract: BAX INHIBITOR-1 (BI-1) is a cell death suppressor widely conserved in plants and animals. Overexpression of BI-1 enhances tolerance to stress-induced cell death in plant cells, although the molecular mechanism behind this enhancement is unclear. We recently found that Arabidopsis ( Arabidopsis thaliana ) BI-1 is involved in the metabolism of sphingolipids, such as the synthesis of 2-hydroxy fatty acids, suggesting the involvement of sphingolipids in the cell death regulatory mechanism downstream of BI-1. Here, we show that BI-1 affects cell death-associated components localized in sphingolipid-enriched microdomains of the plasma membrane in rice ( Oryza sativa ) cells. The amount of 2-hydroxy fatty acid-containing glucosylceramide increased in the detergent-resistant membrane (DRM ; a biochemical counterpart of plasma membrane microdomains) fraction obtained from BI-1-overexpressing rice cells. Comparative proteomics analysis showed quantitative changes of DRM proteins in BI-1-overexpressing cells. In particular, the protein abundance of FLOTILLIN HOMOLOG (FLOT) and HYPERSENSITIVE-INDUCED REACTION PROTEIN3 (HIR3) markedly decreased in DRM of BI-1-overexpressing cells. Loss-of-function analysis demonstrated that FLOT and HIR3 are required for cell death by oxidative stress and salicylic acid, suggesting that the decreased levels of these proteins directly contribute to the stress-tolerant phenotypes in BI-1-overexpressing rice cells. These findings provide a novel biological implication of plant membrane microdomains in stress-induced cell death, which is negatively modulated by BI-1 overexpression via decreasing the abundance of a set of key proteins involved in cell death.